Ringgit Malaysia uncertainty spillover from googles trends uncertainty - Shairil Izwan Taasim; Neilson Anak Teruki; Zainuddin Sabu; Saizal Pinjaman; Robert Abraham Mojolou (RSIS International, 2025)
The great reset of the economic is one of the methods for Malaysia after the crisis of Covid-19 and to boost economic growth again. Meanwhile, Malaysia transitioned to a managed float system, allowing the ringgit to fluctuate based on market conditions. Despite periods of volatility, the economy has demonstrated resilience, supported by prudent monetary and fiscal policies. In 2024, Malaysia experienced strong economic performance, characterized by low and stable inflation. This event motivates us to study the relationship uncertainty from google trends towards ringgit volatility against US Dollar. The study used the Granger causality test methodology to assess the correlation between GTU and Ringgit exchange. The GTU was represented set word in google trends from the uncertainty word from the Economic Report of Malaysia. The data for this study over the period end of the year 2021 (September) until the end of the year 2022 (November). The implication from this study was Google Trends Uncertainty give the impact towards Ringgit volatility in the long run.